Changing selection into full-time work and its effect on wage inequality in Germany - Fitzenberger, Bernd; de Lazzer, Jakob (Empirical Economics, 2022)
To explore whether changes in the selection into full-time work among German men were a driver in the rise in wage inequality since the mid-1990s, we propose a modification of selection-corrected quantile regressions. Addressing Huber and Melly’s (J Appl Econom 30(7):1144–1168, 2015) concerns, this modification allows us to estimate the effects of selection with respect to both observables and unobservables. Our findings show that those employed in 1995 would have had lower wages in 2010 than those employed in 2010 and wage dispersion would have been higher, suggesting that full-time workers have become less heterogeneous over time.
Created from Fastlane, Scopus look-up
Keywords: Full-time employment; Selection into employment; Wage inequality